Synergistic combination of carvedilol, amlodipine, amitriptyline, and antibiotics as an alternative treatment approach for the susceptible and multidrug-resistant A. baumannii infections via drug repurposing - Ugurel, Erennur; Turgut-Balik, Dilek (SPRINGER, 2023)
We evaluated in vitro activity of 13 drugs used in the treatment of some non-communicable diseases via repurposing to determine their potential use in the treatment of Acinetobacter baumannii infections caused by susceptible and multidrug-resistant strains. A. baumannii is a multidrug-resistant Gram-negative bacteria causing nosocomial infections, especially in intensive care units. It has been identified in the WHO critical pathogen list and this emphasises urgent need for new treatment options. As the development of new therapeutics is expensive and time consuming, finding new uses of existing drugs via drug repositioning has been favoured. Antimicrobial susceptibility tests were conducted on all 13 drugs according to CLSI. Drugs with MIC values below 128 & mu;g/mL and control antibiotics were further subjected to synergetic effect and bacterial time-kill analysis. Carvedilol-gentamicin (FICI 0.2813) and carvedilol-amlodipine (FICI 0.5625) were determined to have synergetic and additive effect, respectively, on the susceptible A. baumannii strain, and amlodipine-tetracycline (FICI 0.75) and amitriptyline-tetracycline (FICI 0.75) to have additive effect on the multidrug-resistant A. baumannii strain. Most remarkably, both amlodipine and amitriptyline reduced the MIC of multidrug-resistant, including some carbapenems, A. baumannii reference antibiotic tetracycline from 2 to 0.5 & mu;g/mL, for 4-folds. All these results were further supported by bacterial time-kill assay and all combinations showed bactericidal activity, at certain hours, at 4XMIC. Combinations proposed in this study may provide treatment options for both susceptible and multidrug-resistant A. baumannii infections but requires further pharmacokinetics and pharmacodynamics analyses and in vivo re-evaluations using appropriate models.
Keywords: Acinetobacter baumannii; Antimicrobial resistance; Multidrug resistance; Carbapenem resistance; Drug repurposing; Synergetic effect; ACINETOBACTER-BAUMANNII; ANTIBACTERIAL ACTIVITY; PNEUMONIA; Infectious Diseases; Microbiology